Activation of transient receptor vanilloid 4 increases connexin hemichannel activity in porcine ciliary nonpigmented epithelium - Ek-Vitorin, J. F.; Shahidullah, M.; Delamere, N. A. (Frontiers in Biophysics, 2025)
The ciliary nonpigmented epithelium (NPE) is responsible for the secretion of the aqueous humor into the eye. Indirect evidence from earlier studies raised the possibility that unpaired NPE connexins might form functional hemichannels. Here we used a patch clamp approach to confirm the presence of functional NPE hemichannels on the basis of electrical conductance. We also examined responses to TRPV4 activation because it has been suggested that TRPV4 activation can cause connexin hemichannels to open. Studies using whole-cell (WC) patch clamp showed that hemichannel-like conductance transitions appear spontaneously at a positive holding potential (+80 mV). Most of the transitions fell in the 180–240 pS range expected for fully open Cx43 hemichannels. Activation of TRPV4 channels with the agonist GSK1016790A (10 nM) increased the open probability of the presumptive hemichannels and shifted their conductance toward lower amplitudes. Cell-attached (CA) patch clamp recordings also showed events with low conductance values that signify partially open hemichannels. GSK1016790A exposure also induced depolarization, a response causally associated with hemichannel opening. In studies on coupled pairs of cells, gap junction channel full open conductance amplitudes corresponded to values reported for Cx43, and approximately half the conductance of the observed hemichannel-like events, consistent with the notion that Cx43 is responsible for the observed hemichannels. Taken together, the findings are consistent with NPE hemichannels, formed by Cx43, that open in response to TRPV4 activation. While it seems likely that Ca2+ entry plays a role in the hemichannel response to TRPV4 activation, the depolarization that occurs upon TRPV4 activation might also be important.